Global, regional, and national burdens of congenital heart anomalies from 1990 to 2021, and projections to 2050 - Ye, Erdengqieqieke; Wu, Erman; Tang, Tong; La, Xiaolin (Frontiers in Pediatrics, 2025)
BackgroundCongenital heart anomalies (CHAs) are the most prevalent birth defects, significantly impacting pediatric populations and healthcare systems worldwide. This study provides a comprehensive analysis of the global burden of CHAs, focusing on sex-stratified trends across Socio-Demographic Index (SDI) quintiles from 1990 to 2021.MethodsUtilizing data from the Global Burden of Disease (GBD) study, we assessed sex-disaggregated metrics including prevalence, incidence, mortality, disability-adjusted life years (DALYs), years of life lost (YLLs), and years lived with disability (YLDs) for CHAs in 21 GBD regions and 204 countries.ResultsCHA prevalence and incidence remained stable, with higher incidence in lower SDI regions. Mortality rates, age-standardized DALYs, and YLLs consistently decreased, with males showing higher rates, particularly in low SDI areas. YLDs increased in non-high SDI regions, indicating a growing disability burden. Globally, age-standardized prevalence rates showed a downward trend in countries like China and Ethiopia, while an upward trend was seen in Turkmenistan and Argentina. Incidence rates generally decreased, except in Spain and France. Age-standardized death rates nearly universally declined. YLDs increased in over half of the nations, including Belgium and Spain. Correlation analysis revealed increasing trends of prevalence and YLDs with rising SDI, while incidence, deaths, DALYs, and YLLs demonstrated a declining trend with SDI elevation. From 2022 to 2050, the prevalence of congenital heart anomalies is projected to rise significantly, especially in the 0−4 age group, while mortality rates are expected to continue a slow downward trend, particularly in the 20−69 age group.ConclusionsThe burden of CHAs is influenced by sex and SDI, with a projected increase in prevalence and a continued decline in mortality. The increasing trend of YLDs highlights the need for targeted public health strategies to address the growing disability burden and ensure global health equity.